2002
DOI: 10.1093/oxfordjournals.molbev.a003992
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hematophagy in Ticks: Common Origins for Blood Coagulation and Platelet Aggregation Inhibitors from Soft Ticks of the Genus Ornithodoros

Abstract: Identification and characterization of antihemostatic components from hematophagous organisms are useful for the elucidation of the evolutionary mechanisms involved in adaptation to a highly complex host hemostatic system. Although many bioactive components involved in the regulation of the host's hemostatic system have been described, the evolutionary mechanisms of how arthropods adapted to a blood-feeding environment have not been elucidated. This study describes common origins of both blood coagulation inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
105
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 49 publications
3
105
1
Order By: Relevance
“…Oliveira et al (2010) have summarized the six categories of active molecules from the salivary glands of ticks: 1) prostaglandin (Bowman et al, 1995); 2) histamine band proteins (Arocha-Pinango et al, 1999); 3) platelet aggregation inhibitor (Mans et al, 2002); 4) thrombin inhibitor (Liao et al, 2009); 5) antimicrobial protein (Lai et al, 2004b); and 6) an opioid peptide analog identified from neuroganglion, which is believed to inhibit algesthesia in the host (Lai et al, 2004a,b). The domain that mediates inflammation in the allergic reaction caused by these bioactive molecules is histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al (2010) have summarized the six categories of active molecules from the salivary glands of ticks: 1) prostaglandin (Bowman et al, 1995); 2) histamine band proteins (Arocha-Pinango et al, 1999); 3) platelet aggregation inhibitor (Mans et al, 2002); 4) thrombin inhibitor (Liao et al, 2009); 5) antimicrobial protein (Lai et al, 2004b); and 6) an opioid peptide analog identified from neuroganglion, which is believed to inhibit algesthesia in the host (Lai et al, 2004a,b). The domain that mediates inflammation in the allergic reaction caused by these bioactive molecules is histamine.…”
Section: Discussionmentioning
confidence: 99%
“…Although we know the function for some of these proteins, as indicated above, most of these novel proteins have unknown function. The probable scenario for the evolution of these lipocalins, as proposed for the evolution of BPTI salivary proteins in Ornithodorus ticks (Mans et al, 2002), must have been several events of gene duplication and divergence of function. While lipocalins have also been found in tick saliva performing similar functions as in Rhodnius, such as histamine and serotonin binding (Paesen et al, 2000;Sangamnatdej et al, 2002), this contrasts with mosquitoes and sand flies, where no salivary lipocalins have been described to date, although another family of small ligand-binding proteins, the OBP (Hekmat-Scafe et al, 2000), have evolved into the D7 subfamily found in blood-sucking Diptera (Valenzuela et al, 2002a).…”
Section: Discussionmentioning
confidence: 99%
“…Such expansions are present in both hard and soft ticks but are lineagespecific as they occurred after the divergence of the major tick families. They therefore coincided with the independent adaptation of the hard and soft ticks to a blood-feeding environment (Mans et al, 2002b(Mans et al, , 2008aMans and Neitz, 2004). Such adaptations would have required the evolution of proteins with novel functions that could facilitate blood-feeding behaviour and this was likely the evolutionary stimulus that resulted in the expansion of so many secretory protein families.…”
Section: Discussionmentioning
confidence: 83%
“…These lineage-specific expansions likely occurred during individual adaptations of hard and soft ticks to blood-feeding behaviour after their divergence from the ancestral tick (Mans et al, 2002b(Mans et al, , 2008aMans and Neitz, 2004). It is apparent that the Kunitz protein families are of integral importance to the haematophagous lifestyle of both hard and soft ticks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation